Cerebellar contribution to locomotor behavior: A neurodevelopmental perspective - Sathyanesan, Aaron; Gallo, Vittorio (Neurobiology of learning and memory, 2019)
•Behavior is best understood in the context of neurodevelopment.•Adaptive cerebellar behavior and locomotor behavioral motifs emerge over postnatal development.•The Erasmus Ladder is a robust tool to study adaptive cerebellar behavior in the context of locomotion.•Considerations for development of tools to study cerebellar behavior over postnatal timeline. The developmental trajectory of the formation of cerebellar circuitry has significant implications for locomotor plasticity and adaptive learning at later stages. While there is a wealth of knowledge on the development of locomotor behavior in human infants, children, and adolescents, pre-clinical animal models have fallen behind on the study of the emergence of behavioral motifs in locomotor function across postnatal development. Since cerebellar development is protracted, it is subject to higher risk of genetic or environmental disruption, potentially leading to abnormal behavioral development. This highlights the need for more sophisticated and specific functional analyses of adaptive cerebellar behavior within the context of whole-body locomotion across the entire span of postnatal development. Here we review evidence on cerebellar contribution to adaptive locomotor behavior, highlighting methodologies employed to quantify and categorize behavior at different developmental stages, with the ultimate goal of following the course of early behavioral alterations in neurodevelopmental disorders. Since experimental paradigms used to study cerebellar behavior are lacking in both specificity and applicability to locomotor contexts, we highlight the use of the Erasmus Ladder – an advanced, computerized, fully automated system to quantify adaptive cerebellar learning in conjunction with locomotor function. Finally, we emphasize the need to develop objective, quantitative, behavioral tasks which can track changes in developmental trajectories rather than endpoint measurement at the adult stage of behavior.